Estudo numérico de características de escoamento e transferência de calor em coletor solar de tubo evacuado - Souza, Fábio Ricardo de Oliveira de (Universidade do Vale do Rio dos Sinos, 2013)
This work presents a numerical study on characteristics of flow and heat transfer in an evacuated tube. The numerical approach was performed with the commercial software ANSYS-CFX. The numerical model adopted is three-dimensional and consists of the mass, momentum and energy equations. The computational mesh is hexaedrical, with refinement in regions of higher thermal and fluid gradients. The implemented model was validated with numerical results of literature and a case study was conducted considering inclination angle, rate of heat transfer and water temperature from the thermal reservoir. Also were evaluated two hypotheses: one considering constant physical properties of water and the other with properties varying with temperature. Comparisons are presented for velocity and temperature fields, mass flow and Nusselt and Reynolds numbers. The comparison between the results obtained with the hypothesis of constant properties, with those obtained with variable properties, shows significant differences between them, pointing out the importance of using variable properties in this type of numerical simulation. The results of the parametric studies indicate that the increment of the mass flow and average temperature of the fluid is directly proportional to the inclination angle, the rate of heat transfer and the temperature of the thermal reservoir.
Keywords: Energia solar térmica; Tubo evacuado; Simulação numérica; CFD; Solar thermal energy; Evacuated tube; Numerical simulation; ACCNPQ::Engenharias::Engenharia Mecânica